CEFR VOCABULARY LEVEL FOUND IN GENSHIN IMPACT’S TEYVAT CHAPTER STORYLINE PREVIEW: TRAVAIL - Ahmad Zaelani; Ine` Rahayu Purnamaningsih (IKIP Siliwangi, 2022)
Experts confirmed that vocabulary help learners acquire the four main language skill. Despite its critical role in learning a language, vocabulary is often underestimated and this resulted in confusion among learners about what vocabulary is suitable for their levels. Addressing this, CEFR was established and made the CEFR level vocabulary which are A1, A2, B1, B2, C1, and C2. This article aims to know what vocabulary level is used in the very first of Genshin Impact’s trailer which has 16 million views, hence it will reveal what sort of CEFR vocabulary level needs to fully understand the context given in the trailer. Descriptive research was used and using the EVP (English Vocabulary Profile) as a tool to identify the vocabulary levels. The authors first convert words from spoken form to written form and then analyze them with EVP. A total of 449 of 492 words was found with all levels of CEFR vocabulary levels. While the most frequent is A1 (53%) and the least frequent C1 (3%) appeared. It is important to notice that C2 (5%) also appeared. Thus, it implies that viewers have at least a grasp of the C2 CEFR vocabulary level to fully understand the trailer. Keywords: Vocabulary, CEFR Level, Genshin Impact, Game Trailer